Ez-Zawaf UiTM - Yaakob, Mohd Ashrof Zaki; Saidin, Nurulaina; Bhari, Azri; Khalid, Mohammad Mahyuddin; Mohamed Yusof, Mohd Faiz; Abdullah, Mohd Yusra
EZ-ZAWAF is a digital transformation in the management of zakat, sadaqah and waqf at Universiti Teknologi MARA (UiTM) since the COVID-19 pandemic hit the world. This digitization innovation is implemented through two phases, the first, the phase of adapting changes towards a hybrid digital system, while the second phase focuses on the full implementation of digital systems and the strengthening of new systems implemented. Focus is given to the aspects of zakat, sadaqah and waqf collection that are implemented online, and then the aspects of implementation that are controlled and implemented in synergy and integrity. Next, the evaluation by outcome is made based on the framework of Maqasid Shariah and Sustainable Development Goals (SDGs) in line with the instruments of zakat, sadaqah and waqf implemented at UiTM. Through this management transformation innovation, the management of zakat, sadaqah and waqf in UiTM becomes more efficient, user-friendly and meets the purpose of implementation through the evaluation based on Maqasid Shariah and SDGs. The implementation of EZ-ZAWAF can be the best guide to the management of zakat, sadaqah and waqf in universities throughout Malaysia, and can be a guide in the implementation at the State Islamic Religious Council (SIRC) throughout Malaysia.